Car park designers' handbook - Hill, Jim, 1931-; Rhodes, Glynn; Vollar, Steve (ICE Publishing, 2013)
'Car Park Designers' Handbook' looks at multi-storey car parks as being utilitarian constructions. The authors do not see their design as being a finite art but as a compromise between the motorist's spatial desires and the practical need to achieve economy of construction.